Answer to: "Biomarkers in allergic asthma: Which matrix should we use?". Issue 8 (12th July 2017) - Villaseñor, A.; Rosace, D.; Obeso, D.; Pérez‐Gordo, M.; Chivato, T.; Barbas, C.; Barber, D.; Escribese, M. M.
Abstract : This article is answer to Correspondence published in this issue: DOI:10.1111/cea.12978 .